Portugal : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1995)
This paper reviews economic developments in Portugal during 1990-95. Economic activity rebounded weakly in 1994, growing by 1 percent after a fall of 1.2 percent in 1993. The recession in 1993 was deeper, and the recovery in 1994 weaker than that experienced by the European Union as a whole. Thus, real convergence with Europe was interrupted: although Portuguese GDP per capita increased from 51.4 percent of the European Union average in 1985 to 64.8 percent in 1992, it fell back to 64.4 percent by 1994.